2018
DOI: 10.31557/apjcp.2018.19.12.3635
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Malignant Transformation of Oral Leukoplakia and Oral Lichen Planus Using Laser: An Observational Study

Abstract: Laser intervention prevents recurrence and restricts malignant transformation, and also reduces post-operative dysfunctions. Post-laser therapy recurrence is reported as ranging from 7.7-38.1% and malignant transformation as ranging from 2.6-9% (Ishii et al., 2003; Ishii et al., 2004). The advantages of using laser in treatment of oral lesions includes; the haemostatic effect (giving a clear field of operation), brief therapeutic intervention, reduced traumatization of adjoining tissues (reduced inflammatory

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Most of the studies demonstrated the beneficial effect of LLLT in accelerating the healing process and pain reduction. 22 In the year 2018, Karandeep S A et al 23 conducted an observational study with an aim to evaluate the efficacy of diode laser in the management of homogenous oral leukoplakia (OL) and reticular oral lichen planus (OLP). None of the subjects reported of pain, swelling, or bleeding and it was noted that all the areas treated with laser had healed without scarring with no signs of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies demonstrated the beneficial effect of LLLT in accelerating the healing process and pain reduction. 22 In the year 2018, Karandeep S A et al 23 conducted an observational study with an aim to evaluate the efficacy of diode laser in the management of homogenous oral leukoplakia (OL) and reticular oral lichen planus (OLP). None of the subjects reported of pain, swelling, or bleeding and it was noted that all the areas treated with laser had healed without scarring with no signs of recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Katayama et al (50) applied immunohistochemistry to detect the expression of MMPs and TIMPs in 53 early oral cancer biopsy specimens and reported that the high expression of TIMP-2 was an independent factor for the poor prognosis of early OSCC. Furthermore, Arora et al (51) assessed the expression of type IV collagen in OL and reported that the inhibition of collagen decomposition delayed OL deterioration and tumor spread. The aforementioned evidence suggested that these functions and pathways have specific roles in the progression from OL to OSCC.…”
Section: Fdrsmentioning
confidence: 99%
“…Diode laser (810 nm) has been used to treat oral leukoplakia and oral lichen planus. [ 1 ] CO2 laser has been used in conditions like aphthous ulcers and tissue excesses. [ 2 ] Working with a laser requires safety precautions to avoid accidental exposure.…”
mentioning
confidence: 99%